High temperature corrosion behavior of FeCrAlSi model alloys in the presence of water vapor and KCl at 600 °C – The influence of Cr content. (15th April 2022) - Eklund, J.; Hanif, I.; Bigdeli, S.; Jonsson, T.
Abstract: The corrosion behavior of Fe(5−20)Cr3Al2Si model alloys and the underlying mechanisms after breakaway oxidation was investigated at 600 °C. Rapid breakaway oxidation was triggered for all alloys in the presence of KCl(s). Thermogravimetric analysis showed that alloys with a Cr content of ≥ 10 wt% transitioned into sub-parabolic oxidation kinetics at an early stage of the oxidation process after breakaway oxidation. Through advanced electron/ion microscopy, this behavior was attributed to high Cr-enrichment in the bottom part of the inward-growing scale, indicating the formation of a healing layer. Additionally, alloys with elevated Cr-content (≥15 wt%) were more prone to grain boundary attack. Highlights: The influence of Cr on the corrosion behavior after breakaway oxidation of FeCrAlSi alloys has been investigated. Alloys with a Cr content of ≥ 10 wt% formed slow-growing oxide scales (Fe-rich) after breakaway oxidation. Cr-enrichment observed at the inner part of the slow-growing scales, indicating the formation of a healing layer. Thermodynamic calculations suggest that Cr-enrichment: inhibits internal oxidation; enables formation of a healing layer.